2002
DOI: 10.1002/app.10527
|View full text |Cite
|
Sign up to set email alerts
|

Hemodialysis membrane prepared from cellulose/N‐methylmorpholine‐N‐oxide solution. I. Effect of membrane preparation conditions on its permeation characteristics

Abstract: Flat hemodialysis membranes were prepared from cellulose/N-methylmorpholine-N-oxide (NMMO) solutions (dope) with different cellulose concentrations (6 -8 wt %) by using a phase-inversion method. The coagulant used was NMMO aqueous solution, of which the NMMO concentration and its temperature were varied in the range of 0 to 50 wt % and 5 to 60°C, respectively. The effects of these preparation conditions on the permeation characteristics, the ultrafiltration rate (UFR) of pure water, and sieving coefficient (SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…It is noted that the traditional viscose and cuprammonium route for producing regenerated cellulose films is technologically complex and requires additional facilities for treating the gaseous and aqueous waste emissions (end-of-pipe technology), which constitutes a growing urgency to develop a new pathway to avoid the complicated current routes and hazardous byproducts (Nues and Peinemann 2001;Klemm et al 2005). Thus, an more environmentally friendly process of cellulose membrane preparation has been developed by using a direct solvent system, N-methylmorpholine-N-oxide (NMMO; Fink et al 2001;Zhang et al 2001;Abe and Mochizuki 2002), but the Lyocell process suffers from uncontrolled thermal stability of the system NMMO-cellulose-H 2 O (runaway reaction) and high evaporation costs with energy costs (Fink et al 2001;Zhang et al 2001;Abe and Mochizuki 2002). So far, there has been a lack of a simple and low-cost method for the preparation of regenerated cellulose membrane.…”
Section: Introductionmentioning
confidence: 99%
“…It is noted that the traditional viscose and cuprammonium route for producing regenerated cellulose films is technologically complex and requires additional facilities for treating the gaseous and aqueous waste emissions (end-of-pipe technology), which constitutes a growing urgency to develop a new pathway to avoid the complicated current routes and hazardous byproducts (Nues and Peinemann 2001;Klemm et al 2005). Thus, an more environmentally friendly process of cellulose membrane preparation has been developed by using a direct solvent system, N-methylmorpholine-N-oxide (NMMO; Fink et al 2001;Zhang et al 2001;Abe and Mochizuki 2002), but the Lyocell process suffers from uncontrolled thermal stability of the system NMMO-cellulose-H 2 O (runaway reaction) and high evaporation costs with energy costs (Fink et al 2001;Zhang et al 2001;Abe and Mochizuki 2002). So far, there has been a lack of a simple and low-cost method for the preparation of regenerated cellulose membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The effective membrane area available for ultrafiltration experiments is 38.5 cm 2 . The pure water flux was measured at 37°C at an operating pressure of 250 mmHg [17].…”
Section: Ultrafiltration Rate (Ufr)mentioning
confidence: 99%
“…The solute concentrations in the respective compartments were determined by the Urea Nitrogen (Diacteyl) Reagent method for urea, the Jaffe' method for creatinine, and vitamin B 12 analysis by spectrophotometric at 360 nm for (U-2001, Hitachi Co., Ltd., Tokyo, Japan). The apparent diffusive solute permeability (Pm) of the PSf/PEI blend membranes was calculated as follows [17].…”
Section: Solute Permeability Studiesmentioning
confidence: 99%
“…In a previous article, 23 we reported the effect of coagulation conditions (coagulant temperature and composition) on the ultrafiltration rate (UFR) and sieving coefficient (SC) of a hemodialysis membrane prepared from an NMMO solution. We concluded that the NMMO solution had a possibility of producing a membrane with high performance when coagulation with low-temperature water was employed.…”
Section: Introductionmentioning
confidence: 99%